Empires at war a short history of modern Asia since World War II - Pike, Francis (I. B. Tauris, 2011)
As the major geopolitical power bloc, Asia, with 4 billion people, two thirds of the world's population, a huge land-mass and the fastest growing economies, has shifted the global political balance. This work gives a dramatic narrative account of how Modern Asia came into being. Ranging over the whole of Asia, from Japan to Pakistan, the modern history of this important region is placed in the context of the struggle between America and the Soviet Union. The author shows that America's domination of post war Asia was a continuation of a 100 year competition for power in the region. He also argues that, contrary to the largely "Western centric" viewpoint, Asian nations were not simply the passive and biddable entities of the superpowers, but had a political development which was both separate and unique, with a dynamic that was largely independent of the superpower conflict. And, in conclusion, the book traces the unwinding of American influence and the end of its Empire, a crucial development in international history which is already having repercussions throughout the world.